DEVELOPMENT OF STREET CHILDREN BASED ON THE ART OF ANGKLUNG MUSIC TO SHAPE THE CONFIDENCE OF STREET CHILDREN - Ujang Komara; Sri Nurhayati; Deddy Sulaimawan; Prita Kartika (Kopertis Region IV Jabar and Banten, 2021)
This study aims to describe the process of fostering street children at the An-Nur Ibun Foundation, Bandung Regency. Coaching is done by providing angklung music skills as an effort to increase the self-confidence of street children. This research was conducted using a qualitative approach trying to describe and interpret objects as they are. The research subjects consisted of foundation managers, instructors, and street children who took part in the coaching. Collecting data in this study using observation techniques, interviews, documentation studies, and literature studies. The data analysis in this study is data reduction, data display and conclusion drawing. After conducting the research, it was found that the development of street children carried out at the An-Nur Ibun Foundation as a whole went well, starting with an initial approach, an intense approach, the implementation of coaching through training in playing angklung, and evaluation. After participating in the coaching, street children have better self-confidence such as daring to appear in front of many people, being able to socialize openly, and getting various achievements. Thus, the development of street children based on the skills of angklung music to form this self-confidence can be an alternative in the development of street children's development.